Actualization of SDG-5, SDG-8, and SDG-4 by PT Pertamina Hulu Energi Kampar: A Case Study of the LAPANG PELITA CSR Program (Lapak PKK, Angkringan, and Pustaka Literasi Pertamina) in Bukit Lembah Subur Village - Tasmat, Djulianto; Kuswindriati, Renita Yulia; Isda, Dzakyansyah Naufal (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
In contemporary times, the practice of Corporate Social Responsibility (CSR) by a company in the context of actualizing the Sustainable Development Goals (SDGs) is a necessity. This study aimed to comprehensively explore the efforts made by PT Pertamina Hulu Energi Kampar in actualizing SDGs in the Bukit Lembah Subur Village. The study employed a qualitative methodology with a case study approach. The data utilized in this study consisted of secondary data derived from program implementation reports, monitoring and evaluation reports, as well as relevant articles and journals. The research findings indicate that PT Pertamina Hulu Energi Kampar Field has successfully actualized three SDGs simultaneously through three sub-programs under LAPANG PELITA in the Bukit Lembah Subur Village. First, the Lapak PKK sub-program embodies the actualization of SDG-5 (gender equality) as it has improved the status of women by increasing their income and managerial skills within the PKK member group. Second, the Angkringan sub-program, represented by Adik Kakak MSME, represents the realization of SDG-8 (decent work and economic growth) by providing decent work opportunities for village youth, reducing unemployment rates, and fostering sustainable economic growth. Third, the Pustaka Literasi Pertamina sub-program represents the actualization of SDG-4 (quality education) by providing quality and inclusive education through the Kelompok Taman Baca Langit Ke-7, Rumah Cerdas, and the Digital Library.